Diversity analysis and quantification of lactic acid bacteria in traditionally fermented yaks' milk products from Tibet. Issue 1 (2nd January 2017) - Ren, Yan; Yang, Yanrong; Zhang, Donglei; Wang, Dan; Zhang, Heping; Liu, Wenjun
ABSTRACT: Fermented yaks' milk is a characteristic fermented dairy product with a rich microflora (especially lactic acid bacteria [LAB]), that has been produced by Tibetan people in China throughout history. Systematic analysis of the LAB composition of fermented yaks' milk from central Tibet is essential. In the present study, 38 samples of fermented yaks' milk were collected from three regions in central Tibet. From these, a total of 211 isolates of LAB were generated using traditional pure culture methods. To accurately analyze their biodiversity, 16S rRNA gene sequence analysis and denaturing gradient gel electrophoresis (DGGE) were used. The isolates were identified as belonging to six genera and 22 species/subspecies. Among them, Lactobacillus species predominated (117 isolates) accounting for 55.45% of all isolates. Overall, L. delbrueckii subsp. bulgaricus (60 isolates; 28.43% of the total) was the most commonly isolated species of LAB from fermented yaks' milk from central Tibet. Seven Lactobacillus species and the Bifidobacterium genus were confirmed by quantitative PCR (q-PCR). The q-PCR results showed that the abundance of these groups in fermented yaks' milk from central Tibet ranged from 1.12 ± 0.36 log cfu/ml (for L. sakei from Ningzhong) to 7.77 ± 0.84 log cfu/ml (for L. helvetivus from Ningzhong). Lactobacillus acidophilus, L. delbrueckii subsp. bulgaricus, L. fermentum, L. helveticus varied in concentration depending on the region. The results indicated that traditional fermented yaks' milk from different regions of central Tibet have complex compositions of LAB species. The diversity of LAB might be related to geographical origin.